The Role of Rabbani Youth in the Struggle for Sharia Economic Politics - Musleh Musleh; Dyan Irawati; Mashudi Mashudi (Al-Iffah: Journal of Islamic Sciences Research, 2026)
This article examines the strategic role of Rabbani youth in implementing Islamic economic politics in Indonesia. Rabbani youth, with their understanding and commitment to Islamic values, have great potential to become agents of change in building a strong and sustainable Islamic economic ecosystem. This research will examine the crucial role of Rabbani youth in implementing the Islamic economic political values ​​contained within it. Furthermore, it will discuss their efforts to address the challenges they will face, such as the lack of interest among Rabbani youth in entering politics, the lack of encouragement from religious organizations (NU), and the low level of Islamic financial literacy among the public. Through this approach, Rabbani youth can strive to strengthen their strong networks of understanding and bargaining power, paving the way towards a prosperous and just economic system.